The Quality-Based School Student Management (A SiteStudy at SD Mutual Magelang) - Susilo, Narto (2011)
This study aims to describe (1) characteristics of the quality-based student's academic management in SD Mutual Magelang (2) the characteristics of the qualitybased non-academic student management in SD Mutual Magelang. This type of research is qualitative by ethnography design implemented in SD Mutual Magelang. Resource persons in the study are principal, vice principal, teachersand students. Data collection methods used are depth interviews, observation, and documentation. Analysis of data using an interactive model that begins from (1) data reduction, (2) presentation of data, and (3) inferences. Validity of data include the level of confidence (credibility), transferable (transferability), dependence (dependability), and certainty (Conformability) The results (1) The quality-based student's academic management is conducted through selection of new student, the application of Faculty system, implementation of the reading Qur'an and dhuha prayer together on a regular basis starting at 06:30 to 8:00 p.m., learning to use PAIKEM models and media LCD projector, which is supported by complete learning infrastructure such as computer labs, science, math, and language lab. To improve student achievement, the school set policy and provide crosssubsidies and transportation to student. One academic quality-based management can be seen from the academic achievement of students, one of the academic achievements of students who achieved is the first champion of JSM Olympics and the best skills in computer field and the first champion JSM, Science Olympics; (2) non-academic management carried out by preparing a strategic program and student's talent development program, each student is required to follow the English conversations and ICT club extra, and bring in experts from outside as a teacher in extracurricular activity. One non-academic students can be seen from non-academic achievement of students namely the first runner up Global Art International Drawing and Coloring Competition 2009, the first runner up and the second winner of Garuda Indonesia Junior Essay Competition 2008.